Show that the random variables $X$ and $Y$ are uncorrelated but not independent

The given joint density is

$f(x,y)=1\;\; \text{for } \; -y<x<y \; \text{and } 0<y<1$, otherwise $0$

My main concern here is how should we calculate $f_1(x)$

$f_1(x)=\int_y dy = \int_{-x}^{1}dy + \int_{x}^{1}dy = 1+x +1=2\; \; \forall -1 <x<1$

OR Should we do this?

$f_1(x)$=$$ \begin{cases} \int_{-x}^{1}dy = 1+x && -1<x<0 \\ \int_{x}^{1}dy = 1-x & & 0\leq x <1 \\ \end{cases} $$

In the second case, how do I show they are not independent.

I can directly say that the joint distribution does not have a product space but I want to show that $f(x,y)\neq f_1(x)f_2(y)$

Also, for anyone requiring further calculations,

$f_2(y) = \int dx = \int_{-y}^{y}dx = 2y$

$\mu_2= \int y f_2(y)dy = \int_{0}^{1}2y^2 = \frac23$

$\sigma_2 ^2 = \int y^2f_2(y)dy - (\frac23) ^2 = \frac12 - \frac49 = \frac1{18}$

$E(XY)= \int_{y=0}^{y=1}\int_{x=-y}^{x=y} xy f(x,y)dxdy =\int_{y=0}^{y=1}\int_{x=-y}^{x=y} xy dxdy$ which seems to be $0$? I am not sure about this also.


$f_1(x)=1+x$ if $-1<x<0$ and $1-x$ if $0<x<1$. ( In other words $f_1(x)=1-|x|$ for $|x|<1$). As you have observed $f_2(y)=2y$ for $0<y<1$. Now it is basic fact that if the random variables are independent then we must have $f(x,y)=f_1(x)f_2(y)$ (almost everywhere). Since the equation $(1-|x|)(2y)=f(x,y)$ is not true we can conclude that $X$ and $Y$ are not independent.

$EXY=0$ is correct. Also $EX=\int_{-1}^{1}x(1-|x|)dx=0$ so $X$ and $Y$ are uncorrelated.


A slightly different approach:

The joint density can be written as $$f(x,y)=\underbrace{\frac{1}{2y}\mathbf1_{-y<x<y}}_{f_{X\mid Y=y}(y)}\,\underbrace{2y\mathbf1_{0<y<1}}_{f_Y(y)}$$

Clearly, the (conditional) distribution of $X$ 'given $Y$' depends on $Y$, so that $X$ and $Y$ are not independent.

In fact, $X\mid Y\sim U(-Y,Y)$, which implies $\operatorname{E}(X\mid Y)=0$.


\begin{align} \operatorname{E}\,(XY)&=\operatorname{E}\left[\operatorname{E}\left(XY\mid Y\right)\right] \\&=\operatorname{E}\left[Y\operatorname{E}\left(X\mid Y\right)\right] \\&=\operatorname{E}\left[Y\times 0\right]=0 \end{align}

Also, $$\operatorname{E}(X)=\operatorname{E}\left[\operatorname{E}(X\mid Y)\right]=0$$

This proves that $\operatorname{Cov}(X,Y)=\operatorname{E}(XY)-\operatorname{E}(X)\operatorname{E}(Y)=0$.

  • 1
    $\begingroup$ Downvote for a different method than what OP is following? $\endgroup$ – StubbornAtom May 7 at 6:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.